SISTEM MONITORING LAYANAN KESEHATAN IBU DAN TUMBUH KEMBANG ANAK DI POSYANDU ANGGREK 4 LAGADAR - Sandy Bhawana Mulia; Siti Aminah; Fitria Suryatini; Adhitya Sumardi Sunarya; Sarosa Castrena Abadi (ASOSIASI IDEBAHASA KEPRI, 2023)
The public health monitoring system at the Integrated Service Post (Posyandu) is a form of integrated health service carried out in a Puskesmas working area where the implementation is carried out in each Kelurahan or RW. It can be said that the system is not optimal because during the Covid-19 virus pandemic we have to minimize activities that are physical in nature, such as the use of health books which are currently being used less than optimally for the community because it allows for the spread of the Covid-19 virus. Then the monitoring system still uses email for sending data from Posyandu to Puskesmas, Puskesmas to the Health Office and Health Office to the Ministry of Health. This system is not profitable, because in addition to requiring a lot of time for data transmission, the data sent may fail or not be successfully sent. Solutions related to these problems can be solved by creating a multi-platform-based maternal and child health monitoring system, the monitoring system here can already be done in real time using a database so there is no need for manual data transmission such as via email. In just a few seconds, the data received by the Posyandu from the community will be monitored directly by the Puskesmas, the Health Service and the Ministry of Health. In addition, the data that was previously collected in the form of a book is now replaced with an application that can be opened via a smartphone which contains data along with children's development charts. So that the community and other health care parties can access children's development simply by using a smartphone. In addition, the data will also be managed very well and the data will be maintained when using the application when compared to using a book, the data can be damaged or lost.